Antiplatelet therapy does not influence outcome or host response biomarkers during sepsis: a propensity-matched analysis - Wiewel, MA; De Stoppelaar, SF; Van Vught, LA; Frencken, JF; Hoogendijk, AJ; Klouwenberg, PM Klein; Horn, J; Bonten, MJ; Schultz, MJ; Zwinderman, AH; Cremer, OL; Van der Poll, T (Critical care (London, England), 2015)
Antiplatelet therapy was not related to sepsis severity at presentation, the primary source of infection, causative pathogens, the development of organ failure or shock during ICU stay, or mortality up to 90 days after admission, in either the unmatched or propensity-matched analyses. Acknowledgements This research was performed within the framework of CTMM, the Center for Translational Molecular Medicine (http://www.ctmm.nl), project MARS (grant 04I-201).